Transstadial Transmission of Hepatozoon canis by Rhipicephalus sanguineus (Acari: Ixodidae) in Field Conditions - Aktas, M.; Ozubek, S. (Oxford Univ Press Inc, 2017)
This study investigated possible transovarial and transstadial transmission of Hepatozoon canis by Rhipicephalus sanguineus (Latreille) ticks collected from naturally infected dogs in a municipal dog shelter and the grounds of the shelter. Four hundred sixty-five engorged nymphs were collected from 16 stray dogs that were found to be infected with H. canis by blood smear and PCR analyses and maintained in an incubator at 28 degrees C for moulting. Four hundred eighteen nymphs moulted to adults 14-16 d post collection. Unfed ticks from the shelter grounds comprised 1,500 larvae, 2,100 nymphs, and 85 adults; were sorted according to origin, developmental stage, and sex into 117 pools; and screened by 18S rRNA PCR for Hepatozoon infection. Of 60 adult tick pools examined, 51 were infected with H. canis. The overall maximum likelihood estimate (MLE) of infection rate was calculated as 21.0% (CI 15.80-28.21). Hepatozoon canis was detected in 31 out of 33 female pools (MLE 26.96%, CI 17.64-44.33) and 20 out of 27 male pools (MLE 14.82%, CI 20.15-46.41). Among 42 unfed nymph pools collected from the shelter, 26 were infected with H. canis, and MLE of infection was calculated as 1.9% (CI 1.25-2.77). No H. canis DNA was detected in any of the gDNA pools consisting of larva specimens. Partial sequences of the 18S rRNA gene shared 99-100% similarity with the corresponding H. canis isolates. Our results revealed the transstadial transmission of H. canis by R. sanguineus, both from larva to nymph and from nymph to adult, in field conditions. However, there were no evidence of transovarial transmission.
Keywords: Rhipicephalus sanguineus; Hepatozoon canis; transstadial transmission